Representasi Nilai Optimisme dalam MV PLAVE “The 6th Summer” - Irfiyani, Khoirunnisa; Yoedtadi, Moehammad Gafar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
With the evolution of the digital era, the role of avatars has become increasingly important, and virtual idols have emerged as an important phenomenon in popular culture. Currently, PLAVE has become a popular virtual idol and streamer in South Korea and internationally. In this case, virtual idols often insert various symbols and signs including in MVs. PLAVE's MV